THE GENUS ACROSTICHIDES FONTAINE IN ASIA - Sadovnikov G.N. (My University, 2001)
The validity of the genus Acrostichides Fontaine is argued on the basis of the material from the uppermost Permian of Siberia and the Triassic of China and Iran. The genus and species diagnoses are emended.
Keywords: Triassic; Permian; Палеозой::Пермская; Paleozoic::Permian; Mesozoic::Triassic; Мезозой::Триасовая